Analisis Kualitas Perangkat Lunak Penilaian Kurikulum 2013 Menggunakan Standar ISO/IEC 9126-1:2001 - Noviani Noviani; Muhammad Izman Herdiansyah; Diana Diana (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The 2013 curriculum assessment software is a software that helps facilitate the processing of student grades. This is a routine activity that must be done by teachers to calculate student grades in school. So far there has not been any measurement and analysis of the quality of this assessment software. This study aims to measure and analyze the quality of the 2013 curriculum assessment software based on ISO 9126. The sub-criteria for assessment in the quality attribute are adjusted to 3 external quality criteria of ISO 9126, including functionality, usability and reliability. The sub-criteria and their attributes in each criterion are adjusted to the appearance and procedure of using the 2013 curriculum assessment software and are also based on research that uses user views or perspectives in evaluating the quality of software, especially those of the Software Application type. This study shows the results that the quality characteristics of Functionality have a very strong quality interpretation where the 2013 curriculum assessment software has a product capability level that provides functions that exist in the system and can be implemented and run as expected. For the characteristics of the quality of Usability and Reliability, it shows that the results of quality interpretation are sufficient, it means that the 2013 curriculum assessment Software Operators still find it difficult to understand, operate the software.